Setkání svobodných duchů. Friedrich Nietzsche a Blaise Pascal - Soška, Bernard (Filosoﬁcký časopis)
The text presented here is dedicated to the specific features of Pascal’s thought that Nietzsche pursued in his middle period – especially in the works Human, All Too Human and Dawn of Day. The key question that the author tries to answer is: How does Pascal’s tragic view of the world relate to the negative conception of freedom of Nietzsche’s “free spirits”? In his analysis, the author focuses primarily on the opposition between the concepts of the herd and the contemplative life, as well as on the motifs of distraction, boredom, and despair. Last but not least, the article analyzes Nietzsche’s concept of the strong and predisposed temperament, which he applies specifically to Pascal, Montaigne, and Nietzsche himself. In the conclusion of the study, the author attempts to prove the connection between the process of liberation and healing in all three of the above-mentioned authors.